CHANGE OF BIOCHEMICAL COMPOSITION OF PUMPKIN FRUITS DEPENDING ON STORAGE TIME - A. S. Karapetyan (Овощи России)
Pumpkin fruits are the source of carbohydrates, mineral salts and vitamins during wintertime. The change of the biochemical compositions of pumpkin fruits depending on storage time has been studied. The results of chemical analysis revealed that during four months of storage the content of quality indicators increased followed by its reduction after five and more month of storage.